Ella enchanted [videorecording (DVD)] - O'Haver, Tommy, 1967-; Hathaway, Anne, 1982-; Dancy, Hugh, 1975-; Elwes, Cary, 1962-; Levine, Gail Carson (Miramax Home Entertainment ; Distributed by Buena Vista Home Entertainment, 2004)
Ella lives in a fanciful and magical world where all children are given a "gift" from their fairy Godmother at birth. Ella's gift - and curse - was that of obedience. As a result, Ella cannot refuse any command, and as a result she is often taken advantage of. In a bid to regain control of her life, Ella goes on a quest to free herself from this mysterious "gift". Ella must outwit a kingdom filled with ogres, giants, wicked stepsisters, talking books and other various evil plots.